(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The ways of development and increase of the European Union (EU) exports have been analyzed as the key indicators of economic growth in recent years. The purpose of the article was to determine what particular features and trends in the development of EU export policy contributed to the economic growth and employment rate increase. It has been researched that the network development of EU trade agreements helped to stimulate the European economy, facilitate business and provide jobs. A growing list of strategic agreements has opened up and favored European companies in key markets, helping to promote respect for human rights and labor, as well as environmental standards. The structure and development trends of EU exports, ways to ensure the rights of European exporters, including intellectual property, in international markets were studied. For many years, the EU has moved away from the production of low-cost labor-intensive goods to specialize in goods with higher procession level. The widespread use of information technology has made it possible to trade in goods and services that could not be traded before. The modern world economy has become highly integrated, and global supply chains have largely replaced traditional trade in finished products. Intellectual property protection is crucial to the EU’s ability to stimulate innovation and compete in the global economy. Intellectual property rights enable European inventors, creators and companies to prevent the unauthorized exploitation of their works and to obtain compensation for their investments. Based on the analyzed advantages and achieved economic results, the author substantiated the feasibility of taking into account the EU experience for Ukraine in the development of effective state support for exporters; creation the trade representations network in priority regions for export; expansion of the trade agreements network; focus on the export of high-tech products with high added value and degree of processing; effective protection of domestic exporters and ensuring compliance with the rules of international trade and protection of intellectual property. The development and growth of Ukrainian exports will contribute to economic and employment growth, as well as ensuring sustainable development of Ukraine.